Transcriptional Network Analysis Reveals Drought Resistance Mechanisms of AP2/ERF Transgenic Rice - Ahn, Hongryul; Jung, Inuk; Shin, Seon-Ju; Park, Jinwoo; Rhee, Sungmin; Kim, Ju-Kon; Jung, Woosuk; Kwon, Hawk-Bin; Kim, Sun (Frontiers in Plant Science, 2017)
This study is to investigate at the molecular level how a transgenic version of Nipponbare obtained drought resistance phenotype. Using multi-omics sequencing data, we compared a wild-type version of rice (WT) and a transgenic version of rice (erf71) that obtains drought-resistance phenotype by overexpressing OsERF71, one of the AP2/ERF transcription factor families. A comprehensive bioinformatics analysis pipeline, including transcription factor networks and cascade tree, was developed for the analysis of multi-omics data. The analysis results showed that the presence of OsERF71 at the source of the network controlled global gene expression levels in a specific manner to make erf71 survive longer than WT. Our analysis of the time series transcriptome data suggests that erf71 used more energy to survival-critical mechanisms related to translation, oxidative response, and DNA replication, while further suppressing energy consuming mechanisms such as photosynthesis. To support this hypothesis further, we measured the net photosynthesis level in a physiological condition, which confirmed the further suppression of photosynthesis in erf71. In summary, our work presents a comprehensive snapshot of transcriptional modification of a transgenic version of rice and shows how it induced the rice to acquire drought resistance phenotype.